Antifungal Potential of Sweet Orange Essential Oil on Pathogens of Two Important Cocoa Diseases in Ghana - Yahaya Bukari; Silas Wintuma Avicor; Michael Kojo Ainooson; Eric Kumi Asare; Godfred Kweku Awudzi; Ishmael Amoako-Attah (International Journal of Agronomy)
Plants are known to possess antimicrobial properties, as such, their extracts remain potential sources of eco-friendly antimicrobial products. Extracts from sweet orange have been evaluated as potential antimicrobial sources. However, their activity against pathogens of major agricultural crops such as cocoa is unknown. In this study, the essential oil (EO) of the peel of sweet orange was evaluated against Marasmiellus scandens and Erythricium salmonicolor, the pathogens, respectively, responsible for causing white thread blight and pink disease on cocoa. Minimum Inhibitory Concentration (MIC), IC50, IC90, and IC95 against mycelial growth of the pathogens were determined by agar plate tests following 7 days of incubation. Mycelial growths of the two pathogens were completely (100%) inhibited at 10% (w/v) of the EO. The MIC, IC50, IC90, and IC95 against M. scandens were 0.1%, 0.25%, 1.23%, and 2.11% while those against E. salmonicolor were 0.01%, 0.13%, 0.75%, and 1.35%, respectively. This study shows that EO of sweet orange peel has antifungal activity against the pathogens. Determining the bioactivity of the individual compounds in the EO and field application of effective formulations in future research has potential for the biological control of these fungal diseases of cocoa.